Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1590/2317-1545v43253229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gluconacetobacter diazotrophicus inoculation and reduced nitrogen fertilizer on yield and growth parameters of rice varieties

Abstract: This study aimed to investigate effects of nitrogen (N) fertilizer rates and inoculation of rice seeds with N-fixing bacterium Gluconacetobacter diazotrophicus on the growth parameters and yield of OM5451 and OM6976 rice varieties in the Vietnamese Mekong Delta region. Nitrogen fertilizer rates of 50 kg N.ha-1 and 100 kg N.ha-1 were used, with latter reflecting farmer practice. Three rice seed inoculation methods were also employed: Seeds soaked in water for 24 hours and allowed to stand for 30 hours (control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
2
2
0
Order By: Relevance
“…It explained why the organic carbon and available N contents in the treatment that applied 50 kg N ha -1 did not differ significantly compared to the treatment that applied 100 kg N ha -1 . This results were in agreement with Dung et al (2021) studied the effects of reduced N fertilizer on two rice varieties in the VMD region. Dung et al (2021) reported that applying 50 kg N ha -1 could maintain the number of tillers, rice height, and grain yield of OM5451 and OM6976 compared to the traditional cultivation applied 100 kg N ha -1 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It explained why the organic carbon and available N contents in the treatment that applied 50 kg N ha -1 did not differ significantly compared to the treatment that applied 100 kg N ha -1 . This results were in agreement with Dung et al (2021) studied the effects of reduced N fertilizer on two rice varieties in the VMD region. Dung et al (2021) reported that applying 50 kg N ha -1 could maintain the number of tillers, rice height, and grain yield of OM5451 and OM6976 compared to the traditional cultivation applied 100 kg N ha -1 .…”
Section: Discussionsupporting
confidence: 91%
“…This results were in agreement with Dung et al (2021) studied the effects of reduced N fertilizer on two rice varieties in the VMD region. Dung et al (2021) reported that applying 50 kg N ha -1 could maintain the number of tillers, rice height, and grain yield of OM5451 and OM6976 compared to the traditional cultivation applied 100 kg N ha -1 . pH is the most important factor in the soil has directly affected the availability of soil nutrients (Weil and Brady, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some previous studies showed that the seeds treatments did not significantly affect the rice germinated rate (Adhikari et al, 2013;Hao et al, 2016;Sarkar et al, 2019). In normal conditions, the germination rate of rice depends mainly on the variety (Ju et al, 2000;Dung et al, 2021) Figure 1. The germination rate of rice seeds under different seeds incubation duration…”
Section: The Emergence Rate Of the Rice Seedsmentioning
confidence: 92%
“…Fe-coated primed dry rice seeds, a technology developed in 2004, and untreated rice seeds have both been sown onto paddy fields for comparison studies (Yamauchi, 2004). Some previous studies have shown that a change in the seed inoculation methods did not significantly affect the germination rate of rice seeds (Mori et al, 2012;Adhikari et al, 2013;Hao et al, 2016;Sarkar et al, 2019;Dung et al, 2021;Dung et al, 2022). Mori et al (2012) tested the germination rate of Fe-coated rice seeds under Vietnam Journal of Agricultural Sciences…”
Section: Rice Seed Germination Under Different Rice Seed Methodsmentioning
confidence: 99%